Privacy Dilemmas : Navigating Marketing Strategies in a Post-Cookie Era - Mar'atush Sholihah; Hasti Pramesti Kusnara; Diana Fitri Anggraini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research investigates the dynamics of marketing strategies in the post-cookie era, focusing on PT Indo Pacific as a case study. It examines the influence of consumer privacy concerns and regulatory changes on the adoption and effectiveness of alternative tracking technologies, thereby impacting the overall effectiveness of marketing strategies. Using a quantitative research design with a sample of 60 employees, random sampling, and the Smart PLS tool for analysis, the study reveals significant direct and indirect effects. Results indicate that consumer privacy concerns and regulatory changes significantly influence the adoption of alternative tracking technologies, which in turn affect the effectiveness of marketing strategies. The findings underscore the importance of addressing consumer privacy concerns, complying with regulatory changes, and strategically adopting alternative tracking technologies to enhance marketing effectiveness while respecting privacy and ensuring compliance. These insights offer valuable guidance for businesses navigating the evolving landscape of digital marketing in the post-cookie era.